Increased awareness of medial brachial compartment syndrome is mandatory following endovascular arterial repair - Elizabeth Roderick; Jonathan Gates; Jane Keating (Trauma Case Reports)
Upper extremity compartment syndrome is a rare complication of upper extremity trauma and the entity known as Medial Brachial Fascial Compartment Syndrome is even less so. Given the significant morbidity, both entities must remain a consideration in the management of trauma patients. In the present report, we present a case of Medial Brachial Fascial Compartment Syndrome after endovascular repair of a transected mid-brachial artery.